A robust electro-thermal IGBT SPICE model: Application to short-circuit protection circuit design. Issue 9 (August 2015) - Cavaiuolo, D.; Riccio, M.; Maresca, L.; Irace, A.; Breglio, G.; Daprà, D.; Sanfilippo, C.; Merlin, L.
Abstract: An optimized electro-thermal IGBT SPICE model based on the Kraus model was developed to allow reliable simulation at application level. A particular emphasis to the temperature dependence of physical parameters was given for both the on-state and breakdown conditions. The model was experimentally validated in steady state and transient operation on a Field-Stop trench-gate 30 A–600 V commercial IGBT device. The effectiveness of the convergence–accuracy aspects was proved for the proposed model. The application to the short-circuit protection circuit design for a hard switched fault in an inverter motor-drive application was also analysed. The ability of the proposed IGBT model was experimentally verified with a simplified-equivalent circuit where a short condition was forced on the load, enabling the desaturation protection by the IGBT driver. The results show an accurate prediction of the device electro-thermal behaviour under short-circuit conditions, with a possible optimal design of the desaturation circuit parameters when the device experiences hard-switched-fault or fault-under-load events.